PEMBERDAYAAN ORANG DENGAN GANGGUAN JIWA MELALUI KEGIATAN PEMBUATAN DESINFEKTAN ORGANIK MENGGUNAKAN BAHAN BAKU ECOENZYM - Komala, Encik Putri Ema; Wasalamah, Bardah; Putri, Elsa Lolita; Hermansyah, Oky; Rachmawaty, Suci (Jurnal Abdi Insani, 2025)
Organic waste is abundant around us, including at the Soeprapto Special Mental Hospital (RSKJS) in Bengkulu Province. This organic waste has not been fully utilized at RSKJS in Bengkulu Province, and the service team aims to maximize the utilization of organic waste by empowering People with Mental Disorders (ODGJ) through the production of organic disinfectants using ecoenzyme raw materials. This service activity aims to provide new knowledge and skills to ODGJ so that they are better prepared to reintegrate into society, particularly in the processing of organic waste, namely the production of ecoenzymes. The activities involve education, simulation (practice), and mentoring. The service team coordinates with the psychosocial rehabilitation unit at RSKJS in Bengkulu Province to discuss the current challenges faced by partners, and then develop a plan for producing organic disinfectants using ecoenzyme raw materials. The production of ecoenzymes is carried out entirely by ODGJ, while the production of disinfectants is done by professionals. The results of this service activity include products such as ecoenzymes and organic disinfectants. Keywords: Empowerment, ODGJ, Ecoenzyme, Disinfectant